South African adolescents' lived experiences of acquired hearing loss following multidrug-resistant tuberculosis treatment - Sparg, Tarryn; Petersen, Lucretia; Mayers, Pat; Rogers, Christine (Frontiers in Rehabilitation Sciences, 2024)
Objective: The impact of acquiring hearing loss might be exacerbated during adolescence, as this normal transition from childhood to adulthood is characterised by identity construction and social intensity. This study aimed to describe the lived experiences of South African adolescents with acquired hearing loss following aminoglycoside treatment for multidrug resistant tuberculosis.The study adopted a descriptive phenomenological design and in-depth, semi-structured interviews were conducted in English, isiZulu and Afrikaans. The data was managed and analysed according to a modified version of Hycner's framework.Study sample: Six participants aged 16 to 24 years with bilateral, mild to profound hearing loss acquired from aminoglycoside treatment were recruited from two South African provinces.Results: Three themes emerged which created a triple burden for participants. They endured socioeconomic hardship encompassing limited economic and emotional support. Participants battled the consequences of life-threatening MDR-TB including illness, hospitalisation, stigma, and other challenges. Finally, participants were left with life-changing hearing loss.The findings indicate the necessity of holistic management of adolescents with aminoglycoside-related acquired hearing loss and serves as motivation to improve ototoxic monitoring practices and patient uptake of monitoring services and calls for the cessation, or at least cautious use, of aminoglycosides.